Timing and Distribution of Mitotic Activity in the Retina During Precocial and Altricial Modes of Avian Development - Álvarez-Hernán, Guadalupe; de Mera-Rodríguez, José Antonio; Hernández-Núñez, Ismael; Acedo, Abel; Marzal, Alfonso; Gañán, Yolanda; Martín-Partido, Gervasio; Rodríguez-León, Joaquín; Francisco-Morcillo, Javier (Frontiers in Neuroscience, 2022)
During development of the vertebrate retina, mitotic activity is defined as apical when is located at the external surface of the neuroepithelium or as non-apical when is found in more internal regions. Apical mitoses give rise to all retinal cell types. Non-apical mitoses are linked to committed horizontal cell precursors that subsequently migrate vitreo-sclerally, reaching their final position in the outer surface of the inner nuclear layer, where they differentiate. Previous studies have suggested differences in the timing of retinal maturation between altricial and precocial bird species. In the present study we analyse qualitatively and quantitatively the mitotic activity in the developing retina of an altricial (zebra finch, Taeniopygia guttata) and a precocial (Japanese quail, Coturnix coturnix) bird species. We found that pHisH3-immunoreactive apical and non-apical mitoses were abundant in the T. guttata retina at the hatching stage. In contrast, pHisH3 immunoreactivity almost disappeared from the quail retina at the embryonic day 10 (E10). Furthermore, we also found that the onset of the appearance of non-apical mitoses occurred at later stages in the altricial bird species than in the precocial one. The disappearance of apical mitoses and the spatiotemporal distribution of non-apical mitoses followed central to peripheral and dorsal to ventral gradients, similar to gradients of cell differentiation described in the retina of birds. Therefore, these results suggest that retinal neurogenesis is active at the hatching stage in T. guttata, and that horizontal cell differentiation is delayed in the altricial bird species compared to the precocial one. Together, this study reveals important insights into the timing differences that regulate bird retinal maturation and provides a better understanding of the evolution of avian altriciality and precociality.